Pemberdayaan Masyarakat Dalam Upaya Mandiri Pangan Melalui Hidroponik - Syaifudin, Andang; Astuti, Fitri Puji; Dyana, Hanif; Azam, Abdullah; Fauziah, Alvi; Roshif, Mohammad Qoys; Haikal, Ahmad; Latifah, Afni Nur (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
People's need for food, such as fruit and vegetables, is increasing every year along with population growth. Efforts currently being made to meet the self-sufficient needs of the community's food are by importing, because local products have not been able to meet the food needs of the community due to the not yet optimal level of land productivity in Indonesia so that the hydroponic system is the most appropriate to address food problems because hydroponics is a cultivation system with take advantage of narrow land. The hydroponic training aims to support the introduction of more efficient and sustainable farming methods in the context of limited land and resources and then provide an understanding of farming using the hydroponic method for the people of Candi Baru RT 06/04, Genting village, Boyolali district. The MMK KKN Hydroponic training activities (special mission independent) were held on July 31, 2023. It was held in Dukuh Candi Baru Village, RT 06/04, Kec. Genting district. Boyolali coincided with a local resident's house. The hydroponic technique taught is a simple technique, namely thewick system, plant seeds taught in the hydroponic technique, namely kale, spinach, and bok choy. The results of the questionnaire recap show that the knowledge level of the participants has increased, this is shown by the graph which shows the level of knowledge after the training has increased above 80%. This shows the success of the training carried out by the Mandiri KKN Special Mission UIN Walisongo Semarang for the participants.